Designing trust: how strategic intermediaries choreograph homeowners' low-carbon retrofit experience. Issue 4 (19th May 2019) - de Wilde, Mandy; Spaargaren, Gert
ABSTRACT: In the Netherlands, as in other European countries, the uncertain, fragmented character of the low-carbon retrofit market hampers a transition towards sustainable housing. Connecting homeowners to supply-side actors of low-carbon retrofit procedures, products and technologies in ways satisfactory to homeowners forms an important, challenging task. Service design for the benefit of a customer-centric perspective might be a solution. This paper investigates the potential role of strategic intermediaries as agents of change located between supply-side actors and homeowners. It asks how strategic intermediaries choreograph low-carbon retrofit experiences of homeowners through the design of a 'customer journey'. Trust is a crucial determinant. This paper distinguishes between three customer-journey designs in which, depending on the role envisioned for homeowners, a different trust relation is foregrounded: a private design envisions homeowners as passive consumers who trust in the expertise offered by the intermediary; a civic design envisions homeowners as engaged consumer-citizens who trust their neighbours as reliable service representatives; and a public design envisions homeowners as critical customers who trust in the retrofit technologies and products offered. This implies an important role for policy actors in realizing ways for scaling up and institutionalizing all three low-carbon retrofit customer-journey designs on a national level.